Outcome of Critically Ill COVID-19 Patients After Getting Convalescent Plasma (CP) in ICU of DMCH - Rahman, Ferdous; Islam, Md Tariqul; Ashrafuzzaman , Md; Hossain, Tofazzel; Shafi, Benzir; Ahmed, A S Moudud (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
There are no approved specific antiviral agents or vaccines against COVID-19 till now. In this study, 10critically ill patients confirmed by real-time viral RNA test were enrolled prospectively. One dose of 200mL of convalescent plasma (CP) derived from recently recovered donors with the neutralizing antibodytiters above 1:160 was transfused to the patients as an addition to maximal supportive care and antiviralagents. The aim of this study is to see the outcome of CP transfusion. It was possible to reduce oxygensupport (step down) of 40%(04) patients, 10% (01) patient’s parameters was unchanged and 50% (05)patients were need more oxygen support (step up) after getting CP which correlate with incrementalresponse of lymphocyte counts and detrimental response of biochemical parameters of inflammation.70%(07)patients of total who received mechanical ventilation, after treatment with CP, 30%(03) patients wereweaned from mechanical ventilation to high-flow nasal cannula, and 10%(01) patient discontinued highflownasal cannula to NRM.No severe adverse effects were observed. This study showed CP therapy waswell tolerated and could potentially improve the clinical outcomes through neutralizing viremia in criticalCOVID-19 cases. The optimal dose and time point, as well as the clinical benefit of CP therapy, needsfurther investigation in larger well-controlled trials. JBSA 2021; 34(1): 20-25